Quick firing glaze powder as well as preparation method and application thereof
By using boron, silicon, aluminum, sodium and zirconium sources, the material segregation problem caused by the reduction of glaze viscosity under high temperature conditions is solved, and good adhesion and thermal shock resistance in high temperature environments are achieved.
Patent Information
- Application Number
- CN202510026990.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The viscosity of existing high-temperature glaze powder decreases under high temperature conditions, resulting in material segregation between the glaze and the main phase at high temperature, affecting the stability and stress distribution of the finishing structure.
Boron source, silicon source, aluminum source, sodium source and zirconium source are used as raw materials, and heated to the molten state by a high-frequency induction heating machine and then quenched to obtain the vitreous material, and quick-fired glaze powder is obtained through pulverization, grinding and solid-liquid separation treatment.
The obtained quick-fired glaze powder has good adhesion and thermal shock resistance, and can be used in a high temperature environment of 850°C, avoiding the problem of material segregation between the glaze and the main phase at high temperature.
Smart Images

Figure BDA0005233018240000101 
Figure BDA0005233018240000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glazes and relates to a quick-firing glaze powder and a preparation method and application thereof. Background Art
[0002] Glaze is a dense glassy layer covering the surface of ceramics. With the development of industry, glaze powder is not only limited to the ceramic products industry. Due to its specific physical and chemical properties and improvement of the mechanical properties of the substrate, it is widely used in ceramics, glass and metal industries.
[0003] Glaze can be divided into low-temperature glaze, medium-temperature glaze and high-temperature glaze according to the use temperature. When high-temperature glaze is used as a binder for coating, its sintering range is wide, the high-temperature viscosity is small, and the glaze is severely vitrified, which will lead to poor thermal shock resistance of the coating and easy cracking and falling off.
[0004] CN107226619A discloses an acid-resistant diamond glaze powder comprising: 12-18 parts of Al2O3, 52-66 parts of SiO2, 5-10 parts of CaO, 3-5 parts of K2O, 2-4 parts of Na2O, 3-6 parts of MgO, and 4-8 parts of BaO
[0005] and 2 to 8 parts of ZnO. It includes a frit and a raw material, which are composed of a mass ratio of (5 to 20):100. The method for preparing an acid-resistant diamond glaze comprises the steps of: 1, mixing the raw materials uniformly according to the formula ratio; 2, melting the frit, quenching with water, and crushing; 3, putting the raw material, the frit, sodium carboxymethyl cellulose, sodium tripolyphosphate and water into a ball mill for ball milling to obtain an acid-resistant diamond glaze.
[0006] CN118878211A discloses a secondary sintered microcrystalline ceramic glaze and a preparation method thereof, and a microcrystalline ceramic glaze brick. The method comprises: mixing ingredients according to a predetermined raw material formula and then ball milling to obtain a glaze powder; calcining the glaze powder to obtain a sintered material; mixing ingredients according to a predetermined microcrystalline ceramic glaze formula and grinding them into a glaze slurry, wherein the microcrystalline ceramic glaze formula includes the sintered material; applying the glaze slurry to a brick blank and then secondary calcining to obtain a microcrystalline ceramic glaze.
[0007] The viscosity of the glaze powder obtained by the above scheme is reduced under high temperature conditions, which will cause material segregation between the glaze and the main phase at high temperature, affecting the stability of the finishing structure and stress distribution. Summary of the invention
[0008] The object of the present invention is to provide a quick-fired glaze powder and a preparation method and application thereof. The method of the present invention has simple process steps, strong operability, and low production cost. The quick-fired glaze powder obtained has good adhesion and thermal shock resistance and can be used in a high temperature environment of 850°C.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a quick-fired glaze powder, the method comprising the following steps:
[0011] (1) mixing a boron source, a silicon source, an aluminum source, a sodium source and a zirconium source to obtain a mixed material;
[0012] (2) placing the mixed material in a heating device, heating the mixed material using a high-frequency induction heater, heating the mixed material to a molten state, and then quenching the mixed material to obtain a glass material;
[0013] (3) crushing the glass material to obtain glass powder, mixing the glass powder with a grinding solvent and grinding them to obtain a mixed solution, and performing solid-liquid separation on the mixed solution to obtain the quick-fired glaze powder.
[0014] The present invention uses boron source, silicon source, aluminum source, sodium source and zirconium source as raw materials to prepare glaze powder. In the glaze powder, the introduction of zirconium source promotes the reaction of zirconium oxide with silicon dioxide in the glass phase to generate a large number of zirconium silicate grains with high hardness, increases the crystal phase content, thereby preventing the expansion of cracks and improving the anti-cracking performance of the glaze powder. The glaze powder has strong thermal shock resistance. Using a high-frequency induction heater to heat the mixed material can make the material rise from room temperature to 1300°C in only 2 to 3 minutes, greatly improving the heating rate. The opening level of the original heating device is turned over for a certain period of time before quenching, which is conducive to the material being removed from the heating device after water quenching and cooling.
[0015] Preferably, based on the mass of the mixed material as 100%, the mass fraction of the boron source is 30% to 50%, for example: 30%, 35%, 40%, 45% or 50%, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0016] Preferably, based on the mass of the mixed material as 100%, the mass fraction of the silicon source is 40% to 60%, for example 40%, 45%, 50%, 55% or 60%, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, based on the mass of the mixed material as 100%, the mass fraction of the aluminum source is 5% to 10%, for example 5%, 6%, 7%, 8%, 9% or 10%, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, based on the mass of the mixed material as 100%, the mass fraction of the sodium source is 5% to 10%, for example 5%, 6%, 7%, 8%, 9% or 10%, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] Preferably, based on the mass of the mixed material as 100%, the mass fraction of the zirconium source is 0.1% to 5%, for example, 0.1%, 0.5%, 1%, 2% or 5%, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0020] Preferably, the boron source comprises boron oxide.
[0021] Preferably, the silicon source comprises silicon oxide.
[0022] Preferably, the aluminum source comprises aluminum oxide.
[0023] Preferably, the sodium source comprises sodium bicarbonate.
[0024] Preferably, the zirconium source comprises zirconium oxide.
[0025] Preferably, the material of the mixing device in step (1) includes polytetrafluoroethylene.
[0026] Preferably, the mixing speed in step (1) is 50 rpm to 80 rpm, for example, 50 rpm, 55 rpm, 60 rpm, 70 rpm or 80 rpm, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the mixing time in step (1) is 10 h to 15 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the heating device in step (2) comprises a graphite crucible.
[0029] Preferably, the volume of the mixed material is 30% to 60% of the volume of the heating device, for example 30%, 35%, 40%, 50% or 60%, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, during the heating process in step (2), the temperature of the material is detected by a laser thermometer.
[0031] During the heating process, the temperature of the material is detected by a laser thermometer, and the heating temperature can be more accurately controlled through the data fed back by the laser thermometer, so that the material can be turned and quenched in an optimal molten state to obtain a glass body with complete and uniform crystal structure.
[0032] Preferably, the temperature of the heating treatment in step (2) is 1200°C to 1400°C, for example, 1200°C, 1250°C, 1300°C, 1350°C or 1400°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, after the mixed material is heated to a molten state in step (2), the mixed material undergoes a debubbling phenomenon.
[0034] Preferably, the holding time of the heating treatment in step (2) is 2 min to 3 min, for example, 2 min, 2.2 min, 2.5 min, 2.8 min or 3 min, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0035] Preferably, after heating the mixed material to a molten state in step (2), the heating device is first turned over and then quenching treatment is performed.
[0036] Preferably, the flipping angle of the heating device is 80° to 90°, for example, 80°, 82°, 85°, 88° or 90°, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] The present invention flips the heating device to allow the molten liquid in the device to flow, thereby preventing the crystal from sinking to the bottom and being too tightly combined with the heating device and difficult to separate. The flip angle is the angle between the plane where the opening of the heating device is located and the plane where it is located before flipping.
[0038] Preferably, the holding time for the flipping of the heating device in step (2) is 3s to 5s, for example, 3s, 3.5s, 4s, 4.5s or 5s, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] Preferably, the quenching treatment in step (2) includes placing the molten mixed material and the heating device together in a water quenching tank. After quenching, the mixed material forms a glass material and is directly separated from the heating device.
[0040] Preferably, the pulverizing in step (3) comprises jaw crushing, roller crushing, friction sampling and vibrating screen screening of the glass material in sequence.
[0041] Preferably, the mesh size of the glass powder in step (3) is 200-1000 mesh, for example, 200 mesh, 400 mesh, 600 mesh, 800 mesh or 1000 mesh, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Preferably, the grinding solvent in step (3) comprises any one of ethanol, water, petroleum ether or propanol, or a combination of at least two thereof.
[0043] Preferably, the volume ratio of the glass powder to the solvent in step (3) is 1:(15-25), for example: 1:15, 1:18, 1:20, 1:22 or 1:25, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the material of the device used for grinding in step (3) comprises zirconia ceramics.
[0045] Preferably, the grinding speed in step (3) is 200 rpm to 400 rpm, for example, 200 rpm, 250 rpm, 300 rpm, 350 rpm or 400 rpm, etc., not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0046] Preferably, the grinding time in step (3) is 1 h to 3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0047] Preferably, after obtaining the mixed liquid in step (3), before solid-liquid separation, the mixed liquid is allowed to stand to remove the floating carbon layer on the liquid surface and recover the supernatant.
[0048] Preferably, after the solid-liquid separation in step (3), the obtained solid material is dried.
[0049] Preferably, the drying temperature is 75°C to 85°C, for example, 75°C, 78°C, 80°C, 82°C or 85°C, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0050] Preferably, the drying time is 10 h to 15 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0051] In a second aspect, the present invention provides a quick-fired glaze powder, which is prepared by the preparation method described in the first aspect.
[0052] The quick-fired glaze powder of the present invention can be used in a high temperature environment of 850°C. When used as a binder, the glassy substance mostly exists in the form of isolated islands, so that the coating has good adhesion and thermal shock resistance, and avoids the problem of material segregation between the glaze and the main phase at high temperature (>800°C) due to the decrease in glaze viscosity, which affects the stability of the finishing structure and stress distribution.
[0053] In a third aspect, the present invention provides a metal coating, wherein the metal coating comprises the quick-fired glaze powder as described in the second aspect.
[0054] The quick-fired glaze powder of the present invention is used as a part of an important component of metal coatings and acts on the surface of metal workpieces that require protection against thermal shock and corrosion.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) The method of the present invention has simple process steps, strong operability, and low production cost. The quick-fired glaze powder obtained has good adhesion and thermal shock resistance and can be used in a high temperature environment of 850°C.
[0057] (2) The softening temperature of the quick-fired glaze powder of the present invention can reach below 955°C, the hemispherical temperature can reach below 985°C, the flow temperature can reach below 1035°C, and the thermal expansion coefficient at 20°C to 600°C can reach 5.2×10 -7 / ℃ below, the adhesion level after 1000℃ treatment can reach above 8.8MPa. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0059] Example 1
[0060] This embodiment provides a quick-fired glaze powder, which is prepared by the following method:
[0061] (1) boron oxide, silicon oxide, aluminum oxide, sodium bicarbonate and zirconium oxide were weighed in a mass ratio of 32:55:5:6:2, mixed and placed in a polytetrafluoroethylene ball mill, and stirred at a speed of 60 rpm for 12 hours to obtain a mixed material;
[0062] (2) placing the mixed material in a 50 mL graphite crucible, placing the graphite crucible in a heating coil, heating it with a high-frequency induction heater, detecting the temperature of the material with a laser thermometer, heating the material until it is melted and bubbles appear, the temperature is 1300°C, and the temperature is kept for 2.5 minutes. The entire graphite crucible is clamped with a crucible tongs, turned 90°, and kept for 4 seconds. The crucible is then quickly placed in a water quenching tank for quenching. After the crucible is cooled, the glass material is naturally separated from the graphite crucible;
[0063] (3) After the glass material is enriched, it is crushed by a jaw crusher, a roller crusher, and a friction sampler in sequence, and then sieved to obtain glass powder with a mesh size of 800 mesh. The glass powder is mixed with ethanol in a volume ratio of 1:20 and added to a zirconia ceramic ball mill. The mixture is ball milled at a speed of 300 rpm for 2 hours using a planetary vertical ball mill to obtain a mixed solution. The mixed solution is taken out and allowed to stand for 20 minutes. The floating carbon layer on the liquid surface is skimmed off, the supernatant is recovered, and the precipitate is placed in a drying oven at 80°C and kept warm for 12 hours to obtain the quick-fired glaze powder.
[0064] Example 2
[0065] This embodiment provides a quick-fired glaze powder, which is prepared by the following method:
[0066] (1) boron oxide, silicon oxide, aluminum oxide, sodium bicarbonate and zirconium oxide were weighed in a mass ratio of 39:50:6:4:1, mixed, placed in a polytetrafluoroethylene ball mill, and stirred at a speed of 50 rpm for 15 hours to obtain a mixed material;
[0067] (2) placing the mixed material in a 50 mL graphite crucible, placing the graphite crucible in a heating coil, heating it with a high-frequency induction heater, detecting the temperature of the material with a laser thermometer, heating the material until it is melted and bubbles appear, the temperature is 1200°C, and the temperature is kept for 3 minutes. The entire graphite crucible is clamped with a crucible tongs, turned 80°, and kept for 5 seconds. The crucible is then quickly placed in a water quenching tank for quenching. After the crucible is cooled, the glass material is naturally separated from the graphite crucible;
[0068] (3) After the glass material is enriched, it is crushed by a jaw crusher, a roller crusher, and a friction sampler in sequence, and then sieved to obtain glass powder with a mesh size of 1000. The glass powder is mixed with ethanol in a volume ratio of 1:15 and added to a zirconia ceramic ball mill. The mixture is ball milled at a speed of 200 rpm for 3 hours using a planetary vertical ball mill to obtain a mixed solution. The mixed solution is taken out and allowed to stand for 20 minutes. The floating carbon layer on the liquid surface is skimmed off, the supernatant is recovered, and the precipitate is placed in a drying oven at 85°C and kept warm for 10 hours to obtain the quick-fired glaze powder.
[0069] Example 3
[0070] This embodiment provides a quick-fired glaze powder, which is prepared by the following method:
[0071] (1) boron oxide, silicon oxide, aluminum oxide, sodium bicarbonate and zirconium oxide were weighed in a mass ratio of 33:54:5:7:1, mixed, placed in a polytetrafluoroethylene ball mill, and stirred at a speed of 80 rpm for 10 hours to obtain a mixed material;
[0072] (2) placing the mixed material in a 50 mL graphite crucible, placing the graphite crucible in a heating coil, heating it with a high-frequency induction heater, detecting the temperature of the material with a laser thermometer, heating the material until it is melted and bubbles appear, the temperature is 1400°C, and the temperature is kept for 2 minutes. The entire graphite crucible is clamped with a crucible tongs, turned 95°, and kept for 3 seconds. The crucible is then quickly placed in a water quenching tank for quenching. After the crucible is cooled, the glass material is naturally separated from the graphite crucible;
[0073] (3) After the glass material is enriched, it is crushed by a jaw crusher, a roller crusher, and a friction sampler in sequence, and then sieved to obtain glass powder with a mesh size of 400 mesh. The glass powder is mixed with ethanol in a volume ratio of 1:25 and added to a zirconia ceramic ball mill. The mixture is ball milled at a speed of 400 rpm for 3 hours using a planetary vertical ball mill to obtain a mixed solution. The mixed solution is taken out and allowed to stand for 20 minutes. The floating carbon layer on the liquid surface is skimmed off, the supernatant is recovered, and the precipitate is placed in a 75°C drying oven and kept warm for 15 hours to obtain the quick-fired glaze powder.
[0074] Example 4
[0075] The only difference between this embodiment and embodiment 1 is that the mass fraction of aluminum oxide is 3% (the remaining mass fraction is adjusted with silicon oxide), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0076] Example 5
[0077] The only difference between this embodiment and embodiment 1 is that the mass fraction of aluminum oxide is 12% (the remaining mass fraction is adjusted with silicon oxide), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0078] Example 6
[0079] The difference between this embodiment and embodiment 1 is that the mass fraction of sodium bicarbonate is 3% (the remaining mass fraction is adjusted with silicon oxide), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0080] Example 7
[0081] The difference between this embodiment and embodiment 1 is that the mass fraction of sodium bicarbonate is 12% (the remaining mass fraction is adjusted with silicon oxide), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0082] Example 8
[0083] The only difference between this embodiment and embodiment 1 is that the mass fraction of zirconium oxide is 0.05% (the remaining mass fraction is adjusted with silicon oxide), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0084] Example 9
[0085] The only difference between this embodiment and embodiment 1 is that the mass fraction of zirconium oxide is 8% (the remaining mass fraction is adjusted with silicon oxide), and the other conditions and parameters are exactly the same as those in embodiment 1.
[0086] Comparative Example 1
[0087] The only difference between this comparative example and Example 1 is that the heating is performed by using a high-temperature resistance furnace, and the other conditions and parameters are exactly the same as those in Example 1.
[0088] Comparative Example 2
[0089] The only difference between this comparative example and Example 1 is that sodium bicarbonate is replaced with sodium oxide, and other conditions and parameters are exactly the same as those in Example 1.
[0090] Performance Testing:
[0091] The test equipment is: ① High temperature ceramic melting point tester. After putting the prepared glaze powder into the tester, the temperature at which the material begins to soften is the "softening temperature", the temperature at which the material melts to a certain degree and forms an approximate hemispherical shape is the "hemisphere temperature", and the temperature at which the material flows completely is the "flowing temperature". ② The thermal expansion coefficient of the glaze powder is tested by a horizontal thermal expansion instrument. ③ The adhesion performance of the glaze powder on the metal workpiece is tested by an adhesion tester (pull-off method). The test results are shown in Table 1:
[0092] Table 1
[0093]
[0094]
[0095] As can be seen from Table 1, from Examples 1 to 9, the thermal expansion coefficient of the fast-fired glaze powder of the present invention can reach 8.0×10 -7 / ℃ or less, and the adhesion level after 1000℃ treatment can reach more than 8.0MPa. By adjusting the preparation conditions, the softening temperature of the quick-fired glaze powder can reach below 955℃, the hemispherical temperature can reach below 985℃, the flow temperature can reach below 1035℃, and the thermal expansion coefficient at 20℃~600℃ can reach 5.2×10 -7 / ℃ below, the adhesion level after 1000℃ treatment can reach above 8.8MPa.
[0096] By comparing Example 1 with Examples 4-5, it can be seen that in the preparation process of the quick-fired glaze powder of the present invention, the addition amount of alumina will affect its performance. When the addition amount of alumina is controlled at 5% to 10%, the performance of the quick-fired glaze powder is good. If the addition amount of alumina is too low, the wear resistance of the glaze may be reduced, and the melting and viscosity temperatures may be reduced. If the addition amount of alumina is too high, the melting temperature and high-temperature viscosity will be greatly increased, affecting the sintering process of the glaze powder.
[0097] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the quick-fired glaze powder of the present invention, the addition amount of sodium bicarbonate will affect its performance. When the addition amount of sodium bicarbonate is controlled at 5% to 10%, the performance of the quick-fired glaze powder is better. If the addition amount of sodium bicarbonate is too low, the melting hemispherical temperature and flow temperature of the glaze will be affected. If the addition amount of sodium bicarbonate is too high, the thermal expansion coefficient of the glaze will increase, resulting in crystallization or cracking of the glaze.
[0098] By comparing Example 1 with Examples 8-9, it can be seen that during the preparation process of the quick-fired glaze powder of the present invention, the amount of zirconium oxide added will affect its performance. When the amount of zirconium oxide added is controlled at 0.1% to 5%, the performance of the quick-fired glaze powder is better. If the amount of zirconium oxide added is too low, the thermal expansion coefficient of the glaze increases and the adhesion level decreases, and the acid and alkali resistance of the glaze will also be reduced. If the amount of zirconium oxide added is too high, although the acid and alkali resistance of the glaze can be increased, the resistance to glaze cracking and the glaze hardness will increase, and the adhesion level will be significantly reduced.
[0099] High-frequency induction heating machines generate high-frequency current through electromagnetic induction and use the eddy current effect to generate heat inside the metal, thereby heating or melting the metal. The frequency of high-frequency induction heating machines is generally 15kHz to 450kHz.
[0100] By comparing Example 1 with Comparative Example 1, it can be seen that the present invention uses a high-frequency induction heater to heat the mixed material, which can make the material rise from room temperature to 1300°C in only 2 to 3 minutes, greatly improving the heating rate. In addition, the glaze has a large viscosity. If it takes more than 3 hours to heat it through a high-temperature resistance furnace, the glaze powder cannot be quickly removed from the heating device, and the rapidly cooled liquid adheres to the inside of the heating device, resulting in a greatly reduced yield of the glaze.
[0101] From the comparison between Example 1 and Comparative Example 2, it can be seen that the present invention introduces sodium bicarbonate, and gas is generated during the refining process of glaze powder production, which plays a role in stirring and homogenizing, and at the same time makes the generated sodium oxide more evenly distributed.
[0102] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a quick-fired glaze powder, characterized in that: The preparation method comprises the following steps: (1) mixing a boron source, a silicon source, an aluminum source, a sodium source and a zirconium source to obtain a mixed material; (2) placing the mixed material in a heating device, heating the mixed material using a high-frequency induction heater, heating the mixed material to a molten state, and then quenching the mixed material to obtain a glass material; (3) crushing the glass material to obtain glass powder, mixing the glass powder with a grinding solvent and grinding them to obtain a mixed solution, and performing solid-liquid separation on the mixed solution to obtain the quick-fired glaze powder.
2. The preparation method according to claim 1, characterized in that Taking the mass of the mixed material as 100%, the mass fraction of the boron source is 30% to 50%; Preferably, based on the mass of the mixed material being 100%, the mass fraction of the silicon source is 40% to 60%; Preferably, based on the mass of the mixed material being 100%, the mass fraction of the aluminum source is 5% to 10%; Preferably, based on the mass of the mixed material being 100%, the mass fraction of the sodium source is 5% to 10%; Preferably, based on the mass of the mixed material being 100%, the mass fraction of the zirconium source is 0.1% to 5%; Preferably, the boron source comprises boron oxide; Preferably, the silicon source comprises silicon oxide; Preferably, the aluminum source comprises aluminum oxide; Preferably, the sodium source comprises sodium bicarbonate; Preferably, the zirconium source comprises zirconium oxide.
3. The preparation method according to claim 1 or 2, characterized in that: The material of the mixing device in step (1) includes polytetrafluoroethylene; Preferably, the mixing speed in step (1) is 50 rpm to 80 rpm; Preferably, the mixing time in step (1) is 10 h to 15 h.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The heating device in step (2) comprises a graphite crucible; Preferably, the volume of the mixed material is 30% to 60% of the volume of the heating device; Preferably, during the heating process in step (2), the temperature of the material is detected by a laser thermometer; Preferably, the temperature of the heating treatment in step (2) is 1200° C. to 1400° C.; Preferably, after the mixed material is heated to a molten state in step (2), the mixed material undergoes a bubble removal phenomenon; Preferably, the holding time of the heating treatment in step (2) is 2 min to 3 min.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step (2), after the mixed material is heated to a molten state, the heating device is turned over and then quenching is performed; Preferably, the flip angle of the heating device is 80° to 90°; Preferably, the heating device in step (2) is kept on for 3s to 5s after being turned over; Preferably, the quenching treatment in step (2) includes placing the molten mixed material and the heating device together in a water quenching tank. After quenching, the mixed material forms a glass material and is directly separated from the heating device.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The pulverizing in step (3) includes jaw crushing, roller crushing, friction sampling and vibrating screen screening of the glass material in sequence; Preferably, the mesh size of the glass powder in step (3) is 200 to 1000 mesh.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The grinding solvent in step (3) includes any one of ethanol, water, petroleum ether or propanol, or a combination of at least two thereof; Preferably, the volume ratio of the glass powder to the solvent in step (3) is 1:(15-25); Preferably, the material of the device used for grinding in step (3) comprises zirconia ceramics; Preferably, the grinding speed in step (3) is 200 rpm to 400 rpm; Preferably, the grinding time in step (3) is 1 h to 3 h.
8. The preparation method according to any one of claims 1 to 7, characterized in that: After the mixed liquid is obtained in step (3), before solid-liquid separation, the mixed liquid is allowed to stand for a while, the floating carbon layer on the liquid surface is skimmed off, and the supernatant is recovered; Preferably, after the solid-liquid separation in step (3), the obtained solid material is dried; Preferably, the drying temperature is 75°C to 85°C; Preferably, the drying process takes 10 to 15 hours.
9. A quick-fired glaze powder, characterized in that: The quick-fired glaze powder is prepared by the preparation method according to any one of claims 1 to 8.
10. A metallic coating, characterized in that: The metal paint comprises the quick-fired glaze powder as claimed in claim 9.
Citation Information
Patent Citations
Acid-resistant diamond structure-like glaze powder, its preparation method and preparation method of acid-resistant diamond structure-like glaze ceramic tile
CN107226619A
Secondary sintered microcrystalline ceramic glaze, preparation method thereof and microcrystalline ceramic glaze brick
CN118878211A